Review of landslide inventories for Nepal between 2010 and 2021 reveals data gaps in global landslide hotspot - Erin L. Harvey; Mark E. Kincey; Nick J. Rosser; Arishma Gadtaula; Ethan Collins; Alexander L. Densmore; Alexandre Dunant; Katie J. Oven; Katherine Arrell; Gopi K. Basyal; Megh Raj Dhital; Tom R. Robinson; et al. (Natural Hazards, 2025)
A review of landslide inventories provides an essential assessment of the state of knowledge around landslide hazard and can guide the focus of future studies. This is especially true in Nepal, which is highly prone to landslides, but lacks a comprehensive overview of landslide occurrence nationally. Here, we compile a database of 117 landslide inventories for Nepal released between 2010 and 2021. We review how these existing inventories shape our understanding of landsliding in Nepal and discuss how future research efforts could mitigate current challenges. We find that 40% of the country was only manually mapped once across the study period, and, crucially, these areas did not always correspond with areas of low landslide susceptibility. Instead, existing landslide inventories typically focus on specific areas, such as the region affected by the 2015 Gorkha Earthquake and major highway corridors. We also extrapolated the individual inventory characteristics from within this unique database to infer a national-scale areal density of 0.05 landslides per km 2 , equating to 6000 landslides across the country. This extrapolated value provides a baseline for future national-scale studies, especially for inventories created through automated mapping approaches. Our review highlights the importance of expanding the footprint of landslide inventories in Nepal to include regions with low mapping coverage and the need for inventories to be openly available, with clear protocols to enable inter-comparison. Whilst our review has focused on Nepal, these findings are likely to be relevant in other landslide-prone countries and our recommendations are intended to be applicable elsewhere.